Can graduates increase earnings by acquiring multiple qualifications? - Pushpakumara, T.A.M.; Ranasinghe, A. (University of Colombo, 2017)
According to the Graduates Career Outcome Survey (GCOS) 2011, which was conducted by the Department of Manpower and Employment, Sri Lankan graduates acquire multiple qualifications to upgrade their position in the labour market. A significant number of graduates have followed certificate courses and professional courses other than the degree programme. Hence the objective of this paper is to identify whether acquiring multiple qualifications is an effective strategy for graduates to increase their earnings. To achieve the above objective, a log earnings function was estimated using a national representative data set, GCOS 2011. Graduates’ earnings mainly depend on the type of degree, results, medium of studies, and professional qualifications. The earnings of graduates with First Class Honours is 26% higher than that of others. English-medium graduates earn 22% more than Sinhala- or Tamil-medium graduates. Graduates who have professional qualifications earn 18% more than others. The findings show that a graduate with professional qualifications has a better position in the labour market. There is no return for certificate courses such as English or Tamil language, computing, or management. As findings show that graduate earnings mainly depend on university education, students should prioritize their university education. In the present university system, undergraduates have opportunities to improve their soft skills such as language competence and computer literacy free of charge. Hence, undergraduates should fully utilise the resources available within the university system without engaging in external courses while at university.
Keywords: multiple qualifications, graduate earnings